Peran Ayah Dalam Pembimbingan Pada Perkembangan Kecerdasan Moral Anak (Studi Fenomenologis di Kelas 4 SDN 22 Mataram: Studi Fenomenologis di Kelas 4 SDN 22 Mataram - Maulidiya, Arini (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2025)
This research focuses on the role of fathers in guiding the moral intelligence development of 4th-grade children at SDN 22 Mataram. This focus was chosen based on the increasing significance of the father's role in child development, particularly in the aspect of moral intelligence. Moral intelligence, as defined by Borba, encompasses seven main virtues: empathy, conscience, self-control, respect, kindness, tolerance, and justice. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The research subjects consisted of approximately 3 fathers of students, 2 teachers (class advisors), and 3 students who each met the criteria of still living with their fathers and being willing to participate in this study.The research results show that active father involvement significantly affects the child's moral intelligence. Although busy with work, fathers still take the time to play together, accompany their children while studying, and give advice with a gentle approach without anger or violence. This approach not only strengthens emotional bonds but also instills moral values such as patience, responsibility, and empathy in the child. This proves that the father's role in accompanying and guiding the child is very important for creating an environment that supports the development of positive character. Based on the research findings, it is recommended that fathers remain actively involved in their children's lives despite their busy work schedules. Fathers can take time to play together, accompany their children while studying, and give advice with a gentle approach without using violence. This is important to help instill moral values such as patience, responsibility, and empathy, which contribute to the optimal development of a child's moral intelligence. Keywords: The Role of Father Involvement, Children's Moral Intelligence